2015
DOI: 10.17979/reipe.2015.0.13.490
|View full text |Cite
|
Sign up to set email alerts
|

Uso de plataformas e-learning y alfabetización digital en formación profesional a distancia

Abstract: ResumenLas TIC se han ido incluido progresivamente en la educación. Sin embargo, las investigaciones afirman que esta implementación no ha sido de forma óptima. La literatura respecto a esta temática en la Formación Profesional a distancia es inexistente. Este estudio evalúa el nivel de alfabetización digital y el empleo de las plataformas e-learning en profesores y estudiantes de Formación Profesional a distancia del IES Audiovisual de Vigo. Se empleó la entrevista y el cuestionario. Tras analizar los datos s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
2
0
5
Order By: Relevance
“…In this sense, and focusing on university students, it has been shown that they have an attitude of positive indifference (de Morais et al 2021; AUTHOR) towards this online teaching format; unlike results from Felpeto-Guerrero et al (2015), Robinson et al (2017) and Al-Fraihat et al (2020), who indicated that students valued very highly and were mostly satisfied this form of learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, and focusing on university students, it has been shown that they have an attitude of positive indifference (de Morais et al 2021; AUTHOR) towards this online teaching format; unlike results from Felpeto-Guerrero et al (2015), Robinson et al (2017) and Al-Fraihat et al (2020), who indicated that students valued very highly and were mostly satisfied this form of learning.…”
Section: Discussionmentioning
confidence: 99%
“…In its beginnings, like any resource, it had a series of limitations for both teachers and students. The tools for the creation of evaluation questionnaires, the use of discussion forums or the uploading of video files, and the incorrect reception of messages (Maz et al, 2012;Felpeto-Guerrero et al, 2015) were outlined as conflicting. Today, the difficulties revolve more around the Internet connection, the place where we can connect, and the quality of the materials uploaded by teachers, together with the quality of the content of the debates generated by the students, the organization of group work or online tutoring (AUTHOR), to name the most relevant elements.…”
Section: State Of the Artmentioning
confidence: 99%
“…Outrossim, intervenção psicossocial com os professores contemplando estratégias de coping, saúde mental, questões cognitivas e habilidades para tarefas usando e-learning (Felpeto-Guerrero et al, 2015). Cabe aqui sinalizar as limitações da pesquisa, relacionadas primeiramente a amostra que em sua maioria está composta por mulheres e mães, seria interessante ampliar o estudo e que as diferenças de gênero na composição da amostra não fossem tão dessemelhantes.…”
Section: Relações Entreunclassified
“…En el caso de los alumnos de la Universidad de Córdoba, participantes en este estudio, se manifiestan abiertos a su empleo, por lo que es positiva su percepción de un desarrollo de su proceso de aprendizaje a través de las PTM, en este caso Moodle (Green, Inam y Denton, 2012;Maz, Barcho, Jimenez y Adamuz, 2012;Felpeto, Rey, Fernández-Vázquez y Garrote, 2015;Juhary, 2014;Srichanyachon, 2014), sin embargo, si atendemos al género, vemos que los hombres son los que más se decantan en su participación en este tipo de formación.…”
Section: Conclusionesunclassified
“…Marín Díaz; B. E. SaMpEDro rEquEna; E. VEga gEa pErcEpcionES DE loS EStuDiantES uniVErSitarioS SoBrE laS plataforMaS DE forMación. EStuDio DE caSo De los posibles usos que se le pueden dar a las PTM, los estudiantes señalan que las utilizan fundamentalmente para consultar el programa de la asignatura (Felpeto et al, 2015;Rodríguez y Rivadulla, 2015;Rivadulla, 2015), siendo las mujeres las que más indican su empleo.…”
Section: Conclusionesunclassified